2018
DOI: 10.14218/jcth.2017.00071
|View full text |Cite
|
Sign up to set email alerts
|

Glycosphingolipids Prevent APAP and HMG-CoA Reductase Inhibitors-mediated Liver Damage: A Novel Method for “Safer Drug” Formulation that Prevents Drug-induced Liver Injury

Abstract: Background and Aims: Acetaminophen (APAP) and HMG-CoA reductase inhibitors are common causes of drug-induced liver injury (DILI). This study aimed to determine the ability to reduce APAP- and statins-mediated liver injury by using formulations that combine glycosphingolipids and vitamin E.Methods: Mice were injected with APAP or with statins and treated before and after with β-glucosylceramide (GC), with or without vitamin E. Mice were followed for changes in liver enzymes, liver histology, hepatic expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…The combination therapy of GC and insulin showed a synergistic effect for promoting Akt expression in the liver and alleviating glucose intolerance. An adjuvant effect of GC was previously described in the ob/ob model when co-administered with anti-CD3 [ 31 ] and with other drugs and vaccines [ 25 , 36 ]. These effects were attributed to the potential immunomodulatory effect of GSLs [ 19 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The combination therapy of GC and insulin showed a synergistic effect for promoting Akt expression in the liver and alleviating glucose intolerance. An adjuvant effect of GC was previously described in the ob/ob model when co-administered with anti-CD3 [ 31 ] and with other drugs and vaccines [ 25 , 36 ]. These effects were attributed to the potential immunomodulatory effect of GSLs [ 19 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…β-glucosylceramide was purchased from Avanti Polar Lipids (Alabaster, AL, USA), dissolved in a vehicle of a mixture of 30% Cremophor EL (Sigma, Rehovot,Israel) and ethanol (1 : 1) in PBS, and administered orally by gavage using a designated pipette at a dose of 2.5 mg/kg/day as described [ 21 , 23 , 25 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in halothane-DILI, a pro-inflammatory role of iNKT cells has been suggested, as a greatly reduced neutrophil infiltration was observed in CD1d −/− mice [ 45 ]. Similarly, in APAP-DILI, intrahepatic iNKT cell reduction or loss were associated to either ameliorated disease after treatment with glycosphingolipids and/or vitamin E [ 46 ], or increased glutathione levels and enhanced NAPQI (an APAP reactive metabolite) detoxification [ 47 ]. In contrast, another study showed exacerbated liver damage in both Jα18 −/− and CD1d −/− mice after starvation, and this was associated with CYP2E1 up-regulation and enhanced formation of hepatic APAP-protein adducts, suggesting a protective role of iNKT cells [ 48 ].…”
Section: Immunology Of Dilimentioning
confidence: 99%